Protecting Workers against Unemployment in Uruguay - Veronica Amarante; Rodrigo Arim; Andres Dean (Inter-American Development Bank (IDB), 2011)
This paper considers the main institutional features of the Uruguayan labor market and its recent evolution, with a focus on unemployment. The main policies aimed at protecting workers against unemployment are analyzed. Using administrative data from social security records, the paper studies the dynamics of the labor market. Particularly examined are inflows and outflows from the formal labor market, as well as the effect, in terms of earnings loss, of episodes out of the formal labor market. Finally, an impact evaluation of recent changes in the unemployment insurance program is presented.
Keywords: J01; J08; 330